Factores de riesgo que influyen en el cumplimiento de los controles prenatales en embarazadas adolescentes atendidas en el Centro de Salud By Pass, Babahoyo. Noviembre 2023 – abril 2024. - Gómez Avilés, Karen Jazmín (2024)
The research focuses on analyzing the risk factors affecting compliance with prenatal care in pregnant adolescents attended at the By Pass Health Center in Babahoyo, during the period from November 2023 to April 2024. The importance of addressing this issue is highlighted, given the unique vulnerability of adolescence during pregnancy and the lack of adherence to prenatal care observed in this demographic group. The study is framed within the University's research lines and aims to thoroughly explore determining factors, such as the age of the pregnant women and the potential adverse consequences for maternal and child health. The relevance of identifying and understanding these risk factors to design health intervention strategies tailored to the specific needs of pregnant adolescents is emphasized. The main purpose of the research is to provide valuable information that can lead to improvements in prenatal care and the prevention of obstetric complications. It is hoped that this work will contribute to the advancement of research in maternal and child health, promoting a positive impact on the health of pregnant adolescents and the healthy development of the next generation.